Clobetasol propionate vs. mometasone furoate in 1‐year proactive maintenance therapy of vulvar lichen sclerosus: results from a comparative trial. (22nd April 2015) - Corazza, M.; Borghi, A.; Minghetti, S.; Toni, G.; Virgili, A.
Abstract: Background: Twice‐weekly proactive application of mometasone furoate 0.1% ointment (MMF) over 52 weeks was found to be an effective and safe therapy option in maintaining vulvar lichen sclerosus (VLS) remission and in preventing relapse. Objective: To assess and compare the effectiveness and safety of two different topical corticosteroids, clobetasol propionate 0.05% ointment (CP) and MMF, administered twice weekly as a maintenance therapy of VLS previously stabilized with a topical corticosteroid course. Methods: Forty‐eight patients affected with VLS who had responded to therapy with either CP or MMF in an earlier 12‐week randomized active treatment phase trial were enroled in a 52‐week maintenance phase (MP) to apply their previous treatment twice weekly. The main efficacy parameters were the relapse rate, the mean time of relapse, and the change in symptom and sign severity throughout MP. Results: By the end of the 52‐week MP, 2 (8.33%) subjects among the CP patients and 1 (4.17%) among the MMF patients experienced a relapse; among relapsing patients the mean time to relapse was 30 weeks. Neither subjective nor objective scores changed significantly during MP among CP and MMF patients. No significant differences were found in any of the assessed efficacy endpoints between CP and MMF. Both treatments were well tolerated and the proactive regimen was judged as convenient by patients. Conclusions: Proactive application of the ultra‐potent CP and the potent MMF was found to be an effective, safe and suitable maintenance treatment for long‐term management of VLS. There were no differences between the two corticosteroids.